Mapping Research Trends in Learning IPS of Elementary School: A Bibliometric Analysis - Umar Umar; Haryanto Haryanto (UM Purwokerto Press, 2023)
This study aims to achieve the following objectives: 1) to analyze the publication trends in the field of social studies learning; 2) to identify the journals with the highest number of publications in the area of social studies learning; 3) to assess the productivity of researchers in the field of social studies learning and their contributions to publications; 4) to examine the extent of institutional collaborations in producing publications in social studies learning; 5) to explore the subjects covered in social studies learning publications and their development over time; and 6) to conduct a bibliometric analysis using co-word analysis to map the development of publications in social studies learning based on keywords. The research data was collected through a comprehensive Scopus search using keywords such as learning, social education, and primary school, focusing on article titles, abstracts, and keywords from the period 2013 to 2022. The research trends in social studies learning were analyzed using Vos Viewer software. The findings revealed that the highest number of research publications in the field of social studies learning, indexed in Scopus, was observed in 2022, with 103 publications (14.94%). Most international publications in this field were found in Social Work Education journals, with the United States being the leading contributor. The co-word analysis of the social studies learning field identified eight clusters encompassing 88 themes associated with its development.